Dyadic Models for the Study of Health. Issue 4 (13th March 2013) - Reed, Rebecca G.; Butler, Emily A.; Kenny, David A.
Abstract Dyadic designs have been used in health research to investigate intra‐ and inter‐personal mechanisms of health and well‐being in various types of dyads, including parent–child dyads, siblings, friends, and romantic partners. Although a growing number of researchers are designing studies that capture the interdependent complexities of relationships, many still need more information on how to analyze the data in a way that maximizes its value. Therefore, the purpose of this review paper is twofold: (1) to address some of the ways in which dyadic data analysis is being used in current health research, with an emphasis on research that has employed the Actor‐Partner Interdependence Model, and (2) to propose and explain various methodological and substantive considerations that researchers should consider when using dyadic data analysis in their own research.